2018
DOI: 10.1016/j.molimm.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Parasite allergens

Abstract: Human IgE against helminths is a normal component of the whole protective response elicitesd during infection, when specific IgE to a great number of antigens is produced; however, few of those IgE binding components are actually allergens. In general, considering the strong Th2/IgE responses during helminth infections is intriguing that they are not usually associated with allergic symptoms, which probably (but not exclusively) depends on parasite-induced immunomodulation. However, allergic manifestations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
0
34
0
3
Order By: Relevance
“…Environmental sanitation elements, such as water; sewage, garbage, and waste disposal; sanitary landfills; and garbage treatment, influence the prevalence of parasitosis. These data allow us to associate the lack of sanitary hygiene with the development of dirofilariosis, which may become a socially-determinant public health factor, as in the case of other vector-borne diseases in Colombia, such as malaria, leishmaniosis and Chagas disease (9,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental sanitation elements, such as water; sewage, garbage, and waste disposal; sanitary landfills; and garbage treatment, influence the prevalence of parasitosis. These data allow us to associate the lack of sanitary hygiene with the development of dirofilariosis, which may become a socially-determinant public health factor, as in the case of other vector-borne diseases in Colombia, such as malaria, leishmaniosis and Chagas disease (9,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental sanitation elements, such as water; sewage, garbage, and waste disposal; sanitary landfills; and garbage treatment, influence the prevalence of parasitosis. This data allows us to associate the lack of sanitary hygiene with the development of dirofilariasis, which may become a socially-determinant public health factor, as in the case of other vector-borne diseases in Colombia such as malaria, leishmaniosis and Chagas disease [9,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Anisakis-spoiled fish, such as in sushi, can induce human illness (anisakiasis) with inflammatory intestinal symptoms [12,13]. Anisakis is also causing IgE-mediated allergy to helminth allergens, mostly excretion/secretion parasite molecules [14]. It has been reported that only the ingestion of life parasites leads to clinical symptoms [15].…”
Section: Anisakis-induced Symptomsmentioning
confidence: 99%